None of the above : Puerto Ricans in the global era - Negrón-Muntaner, Frances (New directions in Latino American cultures., 2006)
None of the Above is a state-of-the-art volume about current debates regarding Puerto Rico and Puerto Ricans, both in the United States and on the Island. The title simultaneously refers to the results of a non-binding 1998 plebiscite held to determine the Island's political status, the ambiguities that have historically characterized Puerto Rican political agency, and the complexities of Puerto Rican ethnic, national, and cultural identifications.